Thermodynamic analysis of caustic–roasting of electric arc furnace dust. Issue 10 (October 2022) - Ahmad, Sazzad; Sajal, Wahidur Rahman; Gulshan, Fahmida; Hasan, Mehedi; Rhamdhani, M. Akbar
Abstract: Electric Arc Furnace Dust (EAFD) is a byproduct of the steelmaking industry, which is one of the most significant and rapidly generated hazardous waste. This material includes recyclable elements such as zinc (Zn) and iron (Fe), exclusively in the form of zinc-ferrite (ZnFe2 O4 ), zincite (ZnO), magnetite (Fe3 O4 ) with some other minor compounds of Si, Mn, Mg, and Pb. A combination of pyro and hydrometallurgical route, also known as hybrid process, has acquired considerable attention to extract Fe and Zn from electric arc furnace dust (EAFD). In the current study, systematic thermodynamic assessments using thermochemical–software FactSage and targeted experimental investigations were carried out to assess the suitability of the caustic-roasting step of this important hybrid process. Thermodynamic calculation of the effect of different parameters on the conversion of EAFD to a suitable feedstock for the next separation stages showed that the major zinc-ferrite (ZnFe2 O4 ) phase of EAFD can be potentially converted to ZnO and sodium-ferrite (NaFeO2 ) intermediate phase while reacting with NaOH (>2 mol) at temperatures equal or higher than 100 °C. The suitable condition was assessed to an EAFD to NaOH ratio of 1:3 M fraction and a temperature, T > 318 °C at the normal atmospheric condition. Moreover, the selected experimental investigation was also showing a good agreement with the current thermodynamic assessment. Abstract : Thermodynamics, FactSage, EAFD, Roasting, Recycling.